Dynamics of ecological balance in OECD countries: Sustainable or unsustainable? - Ozcan, Burcu; Danish; Bozoklu, Seref (Elsevier, 2021)
This paper analyzes the sustainability of the per capita ecological balance for 27 OECD countries between 1961 and 2016. In the framework of a quantile unit root test allowing for nonlinearities and asymmetries, we found that, out of the 27 OECD countries, only Germany, Israel, and Mexico have a sustainable ecological balance, while the remaining 24 countries have an unsustainable ecological balance. In addition, the quantile-based results indicate that 13 OECD countries; namely Australia, Austria, France, Germany, Israel, Italy, Luxembourg, Mexico, Poland, Spain, Sweden, the United Kingdom, and the United States have a sustainable ecological balance either at lower or higher quantiles. The sustainability of ecological balance in most OECD countries is likely to become a serious environmental hazard in the near future. Based on the empirical results, some important political actions and steps should be taken to achieve a consensus between economic growth and environmental quality. (C) 2020 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Ecological footprint; Ecological balance; Ecological deficit; Ecological surplus; Quantile unit root test